2024
DOI: 10.1126/sciadv.adk1045
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid biosynthesis is essential for metabolic rewiring during T H 17 cell differentiation

Thiruvaimozhi Abimannan,
Velayoudame Parthibane,
Si-Hung Le
et al.

Abstract: T helper 17 (T H 17) cells are implicated in autoimmune diseases, and several metabolic processes are shown to be important for their development and function. In this study, we report an essential role for sphingolipids synthesized through the de novo pathway in T H 17 cell development. Deficiency of SPTLC1 , a major subunit of serine palmitoyl transferase enzyme complex that catalyzes the first and rate-limiting step of de novo sphingol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…However, numerous PPAR dual/pan agonists have failed to reach clinical practices, because they could not satisfy clinical endpoints (amelioration of e.g., liver injury, fibrosis, steatosis) 31 . It has been reported that lipid metabolism is critical in immune response 32,33 . Conspicuously, our study outlined plausible direct links between metabolism restoration and myeloid cell infiltration in post-SG steatotic rat livers.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous PPAR dual/pan agonists have failed to reach clinical practices, because they could not satisfy clinical endpoints (amelioration of e.g., liver injury, fibrosis, steatosis) 31 . It has been reported that lipid metabolism is critical in immune response 32,33 . Conspicuously, our study outlined plausible direct links between metabolism restoration and myeloid cell infiltration in post-SG steatotic rat livers.…”
Section: Discussionmentioning
confidence: 99%